Legal Issues of Land Rights in Post-Liquefaction Red Zones in Palu City - Yanji, Non Sri Febby; Nurul Miqat; Asri Lasatu (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The designation of red zone areas after the 2018 liquefaction in Palu City has generated complex legal consequences for community land rights. This study examines how the red zone policy affects the legal status and protection of land rights holders and identifies the key normative and empirical problems that hinder the realization of legal certainty in the affected areas. A normative-empirical research design was employed, combining a statutory and conceptual approach with field data obtained from the Palu City Land Office and other relevant stakeholders. Data were analyzed qualitatively using deductive and interpretive legal reasoning. The findings indicate that the implementation of the red zone policy has not yet provided substantive legal certainty, as the government tends to prioritize relocation through permanent housing schemes while pressuring owners to relinquish their civil rights through grant-based mechanisms. The research also reveals juridical disharmony between spatial planning regulations and the guarantee of property rights under agrarian law, resulting in a “frozen” legal status of land and prolonged uncertainty. To restore legal protection, a land acquisition scheme with fair compensation is required as a more coherent and rights-based solution. Keywords: Land Rights; Legal Certainty; Liquefaction; Red Zone